A method for preparing composite honeycomb activated carbon
By surface modification of honeycomb activated carbon and chemical bonding of photocatalysts, composite honeycomb activated carbon was prepared, which solved the problem of saturation of activated carbon adsorption and insufficient binding force of photocatalysts in the prior art, and achieved efficient adsorption and decomposition of formaldehyde.
Patent Information
- Application Number
- CN202411441661.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing honeycomb activated carbon is prone to saturation after adsorption of formaldehyde, and needs to be replaced or regenerated. The binding force of the photocatalyst is insufficient, which makes it easy to fall off in actual applications and difficult to exert decomposition effect.
By treating the finished activated carbon with hydrogen peroxide, the surface polar oxygen-containing groups are enriched, and then the nucleophilic substitution of 3-bromoyl-1-propylene and thiol-ene click reaction is carried out to modify the amino group, and finally with the amino group The titanium dioxide treated with silane coupling agent is chemically bonded by glutaraldehyde as a crosslinking agent to prepare composite honeycomb activated carbon.
It realizes the excellent adsorption and decomposition ability of activated carbon to formaldehyde, and the bonding power between photocatalyst and activated carbon is strong, reducing the shedding and loss of photocatalysts, and is suitable for use in air purifiers.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of activated carbon, and in particular relates to a method for preparing composite honeycomb activated carbon. Background Art
[0002] Air purifiers are a very common device for indoor environments. They can play a very good role in promoting human health. Especially for formaldehyde generated in indoor environments, people often use air purifiers to adsorb it to achieve the purpose of purifying the air. Honeycomb activated carbon is widely used in air purifiers as an adsorption material due to its many advantages such as large specific surface area, small through-hole resistance, developed micropores, and high adsorption capacity. However, the existing honeycomb activated carbon still has many disadvantages that limit its application effect in air purifiers. On the one hand, the honeycomb activated carbon itself only has an adsorption function, and does not decompose and purify formaldehyde. The effect is that it is easy to reach saturation after a period of adsorption and needs to be replaced or regenerated. It is not only troublesome and inconvenient to operate, but also easy to cause secondary pollution of formaldehyde. On the other hand, in order to give the honeycomb activated carbon the function of decomposing and purifying formaldehyde, many existing technologies add photocatalysts to the honeycomb activated carbon, such as titanium dioxide, etc. However, these existing technologies often use physical blending to add the photocatalysts. The binding force between the two is not strong or even non-existent, which leads to the photocatalyst falling off and loss very easily in the actual preparation process or actual application, and ultimately it is difficult to play the desired effect. Summary of the invention
[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a composite honeycomb activated carbon. The present invention starts from the finished activated carbon and first treats it with hydrogen peroxide to enrich its surface with polar oxygen-containing groups such as hydroxyl and carboxyl, and then adds 3-bromo-1-propylene to perform nucleophilic substitution of carboxyl and bromine atoms to modify the double bonds. Then, based on the thiol-ene click reaction, the amino group is modified through the action of mercaptoethylamine, and finally titanium dioxide treated with an aminosilane coupling agent is added. Glutaraldehyde is used as a cross-linking agent to achieve chemical bonding of activated carbon and photocatalyst, thereby preparing a powdered activated carbon composite with a photocatalyst. After mixing, kneading, extrusion molding and drying with conventional substances such as a binder, a composite honeycomb activated carbon is obtained, which not only has excellent adsorption capacity for formaldehyde, but also can decompose it, and is very suitable for application in the field of air purifiers.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing composite honeycomb activated carbon, the preparation method comprising the following steps:
[0006] (1) adding 100 parts by weight of composite supported powdered activated carbon, 4-5 parts by weight of a binder and 25-30 parts by weight of a polytetrafluoroethylene emulsion to 5-8 parts by weight of deionized water, and then stirring and mixing at room temperature for 30-60 minutes to obtain a plastic mud;
[0007] (2) kneading the plastic mud, pouring it into a mold, and extruding it to obtain a honeycomb green body;
[0008] (3) Drying the honeycomb green body at 140-150° C. for 10-12 hours to complete the preparation.
[0009] As a preferred technical solution of the present invention, the composite supported powdered activated carbon in step (1) is prepared by the following steps:
[0010] Step A: adding 4-5 parts by weight of powdered activated carbon to 60-80 parts by weight of hydrogen peroxide, stirring and mixing at 40-50° C. for 2-3 hours, filtering, taking the precipitate, washing with deionized water, and finally vacuum drying at 50-60° C. until constant weight, to obtain oxidatively modified activated carbon;
[0011] Step B: adding the oxidized modified activated carbon and 4-5 parts by weight of 3-bromo-1-propylene to 60-80 parts by weight of an ethanol solution, stirring and mixing at 40-60° C. in the dark for 12-14 hours, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 50-60° C. until constant weight, to obtain olefin-modified activated carbon;
[0012] Step C: adding the olefin-modified activated carbon, 1.5-2 parts by weight of mercaptoethylamine and 0.1-0.3 parts by weight of benzoin dimethyl ether to 80-90 parts by weight of anhydrous ethanol, stirring and mixing at room temperature for 60-80 minutes under ultraviolet light irradiation in a nitrogen atmosphere, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 50-60° C. until constant weight, to obtain amino-modified activated carbon;
[0013] Step D: Add the amino-modified activated carbon, 0.8-1 parts by weight of amino-modified titanium dioxide and 0.3-0.4 parts by weight of glutaraldehyde to 80-90 parts by weight of deionized water, then stir and mix at 60-70°C for 22-24 hours, filter, take the precipitate, wash with deionized water, and finally vacuum dry at 50-60°C until constant weight, and the preparation is completed.
[0014] Furthermore, the powdered activated carbon in step A is at least one of coal-based activated carbon and coconut shell activated carbon; and the particle size of the powdered activated carbon is 50-70 microns.
[0015] Furthermore, the ethanol solution in step B refers to an ethanol aqueous solution; the mass fraction of the ethanol aqueous solution is 60-70%.
[0016] Furthermore, the wavelength of the ultraviolet light in step C is 365nm.
[0017] Furthermore, the amino-modified titanium dioxide in step D is prepared by the following steps:
[0018] Step X: add 0.3-0.5 parts by weight of deionized water, 4-5 parts by weight of anatase nano-titanium dioxide and 0.8-1 parts by weight of an aminosilane coupling agent to 80-100 parts by weight of anhydrous ethanol, then stir and mix at 70-75° C. for 24 hours, filter, take the precipitate, wash with anhydrous ethanol, and finally vacuum dry at 50-60° C. until constant weight, and the preparation is completed.
[0019] Preferably, the particle size of the anatase nano-titanium dioxide in step X is 10-20 nm.
[0020] Preferably, the aminosilane coupling agent in step X is at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
[0021] As a preferred technical solution of the present invention, the binder in step (1) is at least one of carboxymethyl cellulose, hydroxypropyl cellulose, methyl cellulose and polyvinyl alcohol.
[0022] As a preferred technical solution of the present invention, the mud kneading in step (2) refers to kneading the mud for 30 minutes at a vacuum degree of -0.09 MPa.
[0023] As a preferred technical solution of the present invention, the extrusion molding pressure in step (2) is 15-18 MPa.
[0024] Beneficial effects of the present invention:
[0025] (1) The present invention starts with the finished activated carbon and first treats it with hydrogen peroxide to enrich its surface with polar oxygen-containing groups such as hydroxyl and carboxyl groups. Then, 3-bromo-1-propylene is added to perform nucleophilic substitution of carboxyl and bromine atoms to modify the double bonds. Then, based on the thiol-ene click reaction, the amino group is modified through the action of mercaptoethylamine. Finally, titanium dioxide treated with an aminosilane coupling agent is added, and glutaraldehyde is used as a cross-linking agent to achieve chemical bonding of activated carbon and photocatalyst, thereby preparing a powdered activated carbon composited with a photocatalyst. After mixing, kneading, extrusion molding and drying with conventional substances such as a binder, a composite honeycomb activated carbon is obtained, which not only has excellent adsorption capacity for formaldehyde, but also can decompose it, and is very suitable for application in the field of air purifiers.
[0026] (2) The present invention creatively utilizes hydrogen peroxide to oxidatively modify the finished activated carbon, thereby enriching its surface polar oxygen-containing groups. On the one hand, due to the enhancement of the surface polarity, the adsorption capacity of the activated carbon for formaldehyde is further promoted. On the other hand, the active sites of the activated carbon after oxidative modification are increased, which can provide more platforms for the next step of modification treatment. Then, the amino group is modified after the nucleophilic substitution of 3-bromo-1-propylene-mercaptoethylamine click reaction. The introduction of the amino group makes the activated carbon very easy to react with the carbonyl group of formaldehyde, thereby achieving chemical adsorption. At the same time, when glutaraldehyde is used as a cross-linking agent, it can chemically bond with titanium dioxide treated with an aminosilane coupling agent through the action of aldehyde groups and amino groups, so that the photocatalyst is firmly fixed in the activated carbon, which not only gives the activated carbon the ability to decompose formaldehyde under light, but also makes the photocatalyst not easy to fall off or lose. The binding force between the two is strong. In addition, since the surface of the photocatalyst is also rich in amino groups, it further promotes the chemical adsorption of formaldehyde by the activated carbon.
[0027] (3) The composite honeycomb activated carbon prepared by the present invention not only combines physical adsorption and chemical adsorption, but also the photocatalyst is compounded into the activated carbon in the form of chemical bonds. The binding force between the two is strong, and it has excellent adsorption-decomposition ability for volatile organic pollutants, especially formaldehyde, and is very suitable for application in the field of air purifiers. DETAILED DESCRIPTION
[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0029] The polytetrafluoroethylene emulsions in all the embodiments and comparative examples of the present invention were purchased directly from Guangzhou Songbai Chemical Co., Ltd.; the carboxymethyl cellulose was purchased directly from Wen'an Xinbao Cellulose Co., Ltd.; the coal-based activated carbon was sourced from Guangdong Hanyan Activated Carbon Technology Co., Ltd.; the pore density of the composite honeycomb activated carbon was 10 pores / cm 2 The shapes are all cubes and the sizes are all 20mm*20mm*20mm.
[0030] Example 1
[0031] A method for preparing composite honeycomb activated carbon, the preparation method comprising the following steps:
[0032] (1) Adding 100 parts by weight of composite supported powdered activated carbon, 4 parts by weight of a binder and 25 parts by weight of a polytetrafluoroethylene emulsion to 5 parts by weight of deionized water, and then stirring and mixing at room temperature for 30 minutes to obtain a plastic mud;
[0033] (2) kneading the plastic mud, pouring it into a mold, and extruding it to obtain a honeycomb green body;
[0034] (3) Dry the honeycomb green body at 140° C. for 10 hours to complete the preparation.
[0035] The composite supported powdered activated carbon in step (1) is prepared by the following steps:
[0036] Step A: adding 4 parts by weight of powdered activated carbon to 60 parts by weight of hydrogen peroxide, stirring and mixing at 40° C. for 2 h, filtering, taking the precipitate, washing with deionized water, and finally vacuum drying at 50° C. until constant weight, to obtain oxidatively modified activated carbon;
[0037] Step B: adding the oxidized modified activated carbon and 4 parts by weight of 3-bromo-1-propylene to 60 parts by weight of the ethanol solution, stirring and mixing at 40° C. in the dark for 12 h, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 50° C. until constant weight, to obtain olefin-modified activated carbon;
[0038] Step C: adding the olefin-modified activated carbon, 1.5 parts by weight of mercaptoethylamine and 0.1 parts by weight of benzoin dimethyl ether to 80 parts by weight of anhydrous ethanol, stirring and mixing at room temperature for 60 minutes under ultraviolet light irradiation in a nitrogen atmosphere, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 50° C. until constant weight, to obtain amino-modified activated carbon;
[0039] Step D: Add the amino-modified activated carbon, 0.8 parts by weight of amino-modified titanium dioxide and 0.3 parts by weight of glutaraldehyde to 80 parts by weight of deionized water, then stir and mix at 60°C for 22 hours, filter, take the precipitate, wash with deionized water, and finally vacuum dry at 50°C until constant weight, and the preparation is completed.
[0040] The powdered activated carbon in step A is coal-based activated carbon; the particle size of the powdered activated carbon is 50 microns.
[0041] The ethanol solution in step B refers to an ethanol aqueous solution; the mass fraction of the ethanol aqueous solution is 60%.
[0042] The wavelength of the ultraviolet light in step C is 365nm.
[0043] The amino-modified titanium dioxide in step D is prepared by the following steps:
[0044] Step X: Add 0.3 parts by weight of deionized water, 4 parts by weight of anatase nano-titanium dioxide and 0.8 parts by weight of aminosilane coupling agent to 80 parts by weight of anhydrous ethanol, then stir and mix at 70°C for 24 hours, filter, take the precipitate, wash with anhydrous ethanol, and finally vacuum dry at 50°C until constant weight, and the preparation is completed.
[0045] The particle size of the anatase nano-titanium dioxide in step X is 10 nm.
[0046] The aminosilane coupling agent in step X is γ-aminopropyltrimethoxysilane.
[0047] The binder in step (1) is carboxymethyl cellulose.
[0048] The step (2) of kneading the mud refers to kneading the mud for 30 minutes at a vacuum degree of -0.09 MPa.
[0049] The extrusion molding pressure in step (2) is 15 MPa.
[0050] Example 2
[0051] A method for preparing composite honeycomb activated carbon, the preparation method comprising the following steps:
[0052] (1) adding 100 parts by weight of composite supported powdered activated carbon, 5 parts by weight of a binder and 30 parts by weight of a polytetrafluoroethylene emulsion to 8 parts by weight of deionized water, and then stirring and mixing at room temperature for 60 minutes to obtain a plastic mud;
[0053] (2) kneading the plastic mud, pouring it into a mold, and extruding it to obtain a honeycomb green body;
[0054] (3) Dry the honeycomb green body at 150° C. for 12 hours to complete the preparation.
[0055] The composite supported powdered activated carbon in step (1) is prepared by the following steps:
[0056] Step A: adding 5 parts by weight of powdered activated carbon to 80 parts by weight of hydrogen peroxide, stirring and mixing at 50° C. for 3 h, filtering, taking the precipitate, washing with deionized water, and finally vacuum drying at 60° C. until constant weight, to obtain oxidatively modified activated carbon;
[0057] Step B: adding the oxidized modified activated carbon and 5 parts by weight of 3-bromo-1-propylene to 80 parts by weight of the ethanol solution, stirring and mixing at 60° C. in the dark for 14 h, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 60° C. until constant weight, to obtain olefin-modified activated carbon;
[0058] Step C: adding the alkenyl-modified activated carbon, 2 parts by weight of mercaptoethylamine and 0.3 parts by weight of benzoin dimethyl ether to 90 parts by weight of anhydrous ethanol, stirring and mixing at room temperature for 80 minutes under ultraviolet light irradiation in a nitrogen atmosphere, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 60° C. until constant weight, to obtain amino-modified activated carbon;
[0059] Step D: Add the amino-modified activated carbon, 1 part by weight of amino-modified titanium dioxide and 0.4 parts by weight of glutaraldehyde to 90 parts by weight of deionized water, then stir and mix at 70°C for 24 hours, filter, take the precipitate, wash with deionized water, and finally vacuum dry at 60°C until constant weight, and the preparation is completed.
[0060] The powdered activated carbon in step A is coal-based activated carbon; the particle size of the powdered activated carbon is 70 microns.
[0061] The ethanol solution in step B refers to an ethanol aqueous solution; the mass fraction of the ethanol aqueous solution is 70%.
[0062] The wavelength of the ultraviolet light in step C is 365nm.
[0063] The amino-modified titanium dioxide in step D is prepared by the following steps:
[0064] Step X: Add 0.5 parts by weight of deionized water, 5 parts by weight of anatase nano-titanium dioxide and 1 part by weight of an aminosilane coupling agent to 100 parts by weight of anhydrous ethanol, then stir and mix at 75°C for 24 hours, filter, take the precipitate, wash it with anhydrous ethanol, and finally vacuum dry it at 60°C until constant weight, and the preparation is completed.
[0065] The particle size of the anatase nano-titanium dioxide in step X is 20 nm.
[0066] The aminosilane coupling agent in step X is γ-aminopropyltrimethoxysilane.
[0067] The binder in step (1) is carboxymethyl cellulose.
[0068] The step (2) of kneading the mud refers to kneading the mud for 30 minutes at a vacuum degree of -0.09 MPa.
[0069] The extrusion molding pressure in step (2) is 18 MPa.
[0070] Example 3
[0071] A method for preparing composite honeycomb activated carbon, the preparation method comprising the following steps:
[0072] (1) adding 100 parts by weight of composite supported powdered activated carbon, 4.5 parts by weight of a binder and 28 parts by weight of a polytetrafluoroethylene emulsion to 7 parts by weight of deionized water, and then stirring and mixing at room temperature for 45 minutes to obtain a plastic mud;
[0073] (2) kneading the plastic mud, pouring it into a mold, and extruding it to obtain a honeycomb green body;
[0074] (3) The honeycomb green body is dried at 145° C. for 11 hours to complete the preparation.
[0075] The composite supported powdered activated carbon in step (1) is prepared by the following steps:
[0076] Step A: adding 4.5 parts by weight of powdered activated carbon to 70 parts by weight of hydrogen peroxide, stirring and mixing at 45° C. for 2.5 hours, filtering, taking the precipitate, washing with deionized water, and finally vacuum drying at 55° C. until constant weight, to obtain oxidatively modified activated carbon;
[0077] Step B: adding the oxidized modified activated carbon and 4.5 parts by weight of 3-bromo-1-propylene to 70 parts by weight of the ethanol solution, stirring and mixing at 50° C. in the dark for 13 h, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 55° C. until constant weight, to obtain olefin-modified activated carbon;
[0078] Step C: adding the alkenyl-modified activated carbon, 1.7 parts by weight of mercaptoethylamine and 0.2 parts by weight of benzoin dimethyl ether to 85 parts by weight of anhydrous ethanol, stirring and mixing at room temperature for 70 minutes under ultraviolet light irradiation in a nitrogen atmosphere, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 55° C. until constant weight, to obtain amino-modified activated carbon;
[0079] Step D: Add the amino-modified activated carbon, 0.9 parts by weight of amino-modified titanium dioxide and 0.35 parts by weight of glutaraldehyde to 85 parts by weight of deionized water, then stir and mix at 65°C for 23 hours, filter, take the precipitate, wash with deionized water, and finally vacuum dry at 55°C until constant weight, and the preparation is completed.
[0080] The powdered activated carbon in step A is coal-based activated carbon; the particle size of the powdered activated carbon is 60 microns.
[0081] The ethanol solution in step B refers to an ethanol aqueous solution; the mass fraction of the ethanol aqueous solution is 65%.
[0082] The wavelength of the ultraviolet light in step C is 365nm.
[0083] The amino-modified titanium dioxide in step D is prepared by the following steps:
[0084] Step X: Add 0.4 parts by weight of deionized water, 4.5 parts by weight of rutile nano-titanium dioxide and 0.9 parts by weight of aminosilane coupling agent to 90 parts by weight of anhydrous ethanol, then stir and mix at 73°C for 24 hours, filter, take the precipitate, wash with anhydrous ethanol, and finally vacuum dry at 55°C until constant weight, and the preparation is completed.
[0085] The particle size of the anatase nano-titanium dioxide in step X is 15 nm.
[0086] The aminosilane coupling agent in step X is γ-aminopropyltrimethoxysilane.
[0087] The binder in step (1) is carboxymethyl cellulose.
[0088] The step (2) of kneading the mud refers to kneading the mud for 30 minutes at a vacuum degree of -0.09 MPa.
[0089] The extrusion molding pressure in step (2) is 17 MPa.
[0090] Comparative Example 1
[0091] Based on Example 1, the hydrogen peroxide in step A was replaced by an equal weight of deionized water, and the rest remained unchanged.
[0092] Comparative Example 2
[0093] Based on Example 1, glutaraldehyde in step D was replaced with an equal weight of deionized water, and the rest remained unchanged.
[0094] Comparative Example 3
[0095] Based on Example 1, the amount of aminosilane coupling agent in step X was changed to 0.6 parts by weight, and the rest remained unchanged.
[0096] Test Example 1
[0097] Adsorption-decomposition test:
[0098] The composite honeycomb activated carbon prepared in Examples 1-3 and Comparative Examples 1-3 were placed in a 1 m 3 A sealed box (containing air) was placed in the room, and then 12 mg of formaldehyde gas was introduced into each of them in a dark environment. After 8 hours, the saturated adsorption capacity was reached. The composite honeycomb activated carbon was taken out, and the formaldehyde concentration in the sealed box was detected by gas chromatograph to calculate the formaldehyde removal rate.
[0099] The composite honeycomb activated carbon prepared in Examples 1-3 and Comparative Examples 1-3 were placed in a 1 m 3The composite honeycomb activated carbon was taken out and the formaldehyde concentration in the sealed box was detected by gas chromatograph to calculate the formaldehyde removal rate.
[0100] Table 1. Adsorption-decomposition test results
[0101]
[0102] Comparison between Example 1 and Comparative Examples 1-3 shows that:
[0103] The difference between Comparative Example 1 and Example 1 is that the comparative example 1 is not subjected to oxidation treatment with hydrogen peroxide.
[0104] The difference between Comparative Example 2 and Example 1 is that glutaraldehyde is not used as a cross-linking agent to achieve chemical bonding between activated carbon and photocatalyst.
[0105] The difference between Comparative Example 3 and Example 1 is that the number of amino groups on the surface of the photocatalyst is reduced.
[0106] From Test Example 1, as shown in Table 1, it can be seen from the comparison between Example 1 and Comparative Examples 1-3 that the composite honeycomb activated carbon prepared by the present invention has excellent adsorption and decomposition effects on formaldehyde. At the same time, the binding force between the photocatalyst and the activated carbon is strong and is not easy to cause loss.
[0107] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite honeycomb activated carbon, characterized in that: The preparation method comprises the following steps: (1) adding 100 parts by weight of composite supported powdered activated carbon, 4-5 parts by weight of a binder and 25-30 parts by weight of a polytetrafluoroethylene emulsion to 5-8 parts by weight of deionized water, and then stirring and mixing at room temperature for 30-60 minutes to obtain a plastic mud; (2) kneading the plastic mud, pouring it into a mold, and extruding it to obtain a honeycomb green body; (3) drying the honeycomb green body at 140-150° C. for 10-12 hours, and the preparation is completed; The composite supported powdered activated carbon in step (1) is prepared by the following steps: Step A: adding 4-5 parts by weight of powdered activated carbon to 60-80 parts by weight of hydrogen peroxide, stirring and mixing at 40-50° C. for 2-3 hours, filtering, taking the precipitate, washing with deionized water, and finally vacuum drying at 50-60° C. until constant weight, to obtain oxidatively modified activated carbon; Step B: adding the oxidized modified activated carbon and 4-5 parts by weight of 3-bromo-1-propylene to 60-80 parts by weight of an ethanol solution, stirring and mixing at 40-60° C. in the dark for 12-14 hours, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 50-60° C. until constant weight, to obtain olefin-modified activated carbon; Step C: adding the olefin-modified activated carbon, 1.5-2 parts by weight of mercaptoethylamine and 0.1-0.3 parts by weight of benzoin dimethyl ether to 80-90 parts by weight of anhydrous ethanol, stirring and mixing at room temperature for 60-80 minutes under ultraviolet light irradiation in a nitrogen atmosphere, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 50-60° C. until constant weight, to obtain amino-modified activated carbon; Step D: adding the amino-modified activated carbon, 0.8-1 parts by weight of amino-modified titanium dioxide and 0.3-0.4 parts by weight of glutaraldehyde to 80-90 parts by weight of deionized water, stirring and mixing at 60-70° C. for 22-24 hours, filtering, taking the precipitate, washing with deionized water, and finally vacuum drying at 50-60° C. until constant weight, and the preparation is completed; The amino-modified titanium dioxide in step D is prepared by the following steps: Step X: adding 0.3-0.5 parts by weight of deionized water, 4-5 parts by weight of anatase nano-titanium dioxide and 0.8-1 parts by weight of an aminosilane coupling agent to 80-100 parts by weight of anhydrous ethanol, and then stirring and mixing at 70-75° C. for 24 hours, filtering, taking the precipitate, washing with anhydrous ethanol, and finally vacuum drying at 50-60° C. until constant weight, the preparation is completed; The particle size of the anatase nano-titanium dioxide in step X is 10-20 nm; The aminosilane coupling agent in step X is at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
2. The method for preparing a composite honeycomb activated carbon according to claim 1, characterized in that: The powdered activated carbon in step A is at least one of coal-based activated carbon and coconut shell activated carbon; the particle size of the powdered activated carbon is 50-70 microns.
3. The method for preparing a composite honeycomb activated carbon according to claim 1, characterized in that: The ethanol solution in step B refers to an ethanol aqueous solution; the mass fraction of the ethanol aqueous solution is 60-70%.
4. The method for preparing a composite honeycomb activated carbon according to claim 1, characterized in that: The binder in step (1) is at least one of carboxymethyl cellulose, hydroxypropyl cellulose, methyl cellulose and polyvinyl alcohol.
5. The method for preparing a composite honeycomb activated carbon according to claim 1, characterized in that: The step (2) of kneading the mud refers to kneading the mud for 30 minutes at a vacuum degree of -0.09 MPa.
6. The method for preparing a composite honeycomb activated carbon according to claim 1, characterized in that: The extrusion molding pressure in step (2) is 15-18 MPa.
Citation Information
Patent Citations
Preparation method for cationic-type activated carbon
CN102806073A
Preparation method of nanometer titanium dioxide / loofah sponge composite photocatalyst
CN104624243A
A multifunctional air purification honeycomb composite material
CN109865424A